2017
DOI: 10.1186/s12909-017-1015-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining patterns in medication documentation of trade and generic names in an academic family practice training centre

Abstract: BackgroundStudies in the United States have shown that physicians commonly use brand names when documenting medications in an outpatient setting. However, the prevalence of prescribing and documenting brand name medication has not been assessed in a clinical teaching environment. The purpose of this study was to describe the use of generic versus brand names for a select number of pharmaceutical products in clinical documentation in a large, urban academic family practice centre.MethodsA retrospective chart re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
14
2
Order By: Relevance
“…A 2012 survey of prescribers found that the majority of prescribers rarely asked about a patient's prescription insurance coverage or consulted a drug list before writing a prescription [ 17 ]. Physicians' use and documentation of contraceptives' brand names rather than their generic names may also lead to promotion of brand-name contraceptive use when generic alternatives are available [ 18 , 19 ]. There may be information system technologies that could help providers access drug pricing information to help guide cost-conscious clinical decision making [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 survey of prescribers found that the majority of prescribers rarely asked about a patient's prescription insurance coverage or consulted a drug list before writing a prescription [ 17 ]. Physicians' use and documentation of contraceptives' brand names rather than their generic names may also lead to promotion of brand-name contraceptive use when generic alternatives are available [ 18 , 19 ]. There may be information system technologies that could help providers access drug pricing information to help guide cost-conscious clinical decision making [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature on medication name usage in humanauthored text suggests that trade names are more commonly used than generic names. (Steinman et al, 2007;Summers et al, 2017) This raises the possibility that the trend toward generally more subjective (both greater negative and positive sentiment) trade name documents may be the result of individual authors' tendency to use the more memorable or evocative name, whereas less subjective standardized medication catalogs and treatment information sites may be more commonly captured in the generic name sample. More recent medications not yet available in generic form may also be referenced by marketing efforts, with greater positive sentiment on industry-supported web pages optimized to appear at the top of Internet searches.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of time in the crowded OPDs, and ease of documentation can also contribute to the latter fact. 27 Various national and international regulatory bodies recommend generic drug prescribing for the above mentioned reasons. 28 The percentage of drugs prescribed from essential drug list in our center was 87.9 %, (WHO standards 100%) which indicates fairly enough drugs were prescribed from the essential medicine list.…”
Section: Discussionmentioning
confidence: 99%